Association between vitamin D, vitamin D supplementation and benign paroxysmal positional vertigo: a systematic review and meta-analysis - Li, Yanyan; Gao, Peng; Ding, Rui; Xu, Ying; Wang, Zhicheng; Pei, Xiaorui; Li, Lianhe (Frontiers in Neurology, 2025)
BackgroundBenign paroxysmal positional vertigo (BPPV) is one of the most prevalent peripheral vestibular dysfunctions encountered in clinical practice, including dizziness and vertigo, which has a significant impact on people’s everyday lives and affects their quality of life in many ways. Researches indicate that individuals with recurrent benign paroxysmal positional vertigo (BPPV) may exhibit vitamin D insufficiency, and certain studies suggest that correcting severe vitamin D deficiency might effectively reduce BPPV recurrence; nevertheless, the findings have been inconsistent. As a result, we conducted the current Meta-analysis to investigate potential associations of vitamin D levels with the occurrence and recurrence of BPPV. In the meantime, the current study was done to evaluate the impact of vitamin D supplementation on the prevention of benign paroxysmal positional vertigo recurrence.MethodsElectronic databases (PubMed, EMBASE, SCOPUS and the Cochrane Library) were identified to search for relevant studies about (vitamin D or vitamin D supplementation) and (Benign paroxysmal positional vertigo incidence or recurrence) from inception to Dec 22, 2024. 60 studies with a total of 16,368 participants were included into this meta-analysis.Results(1) The aggregated weighted mean difference (WMD) demonstrated that there was a significant reduction in vitamin D level in the BPPV cohort (WMD = −2.84; 95% CI −4.53 to −1.15) relative to the control cohort. Likewise, Recurrent BPPV groups had significantly lower levels of vitamin D compared to non-recurrent groups (WMD = −5.01; 95% CI −6.94 to −3.08). When the cupulolithiasis BPPV groups were compared to the canalolithiasis BPPV groups, the vitamin D level was lower in the cupulolithiasis groups (WMD = 5.09; 95% CI 2.05 to 8.12); (2) In this meta-analysis, the multivariable-adjusted relative risk (RR) indicated that increased vitamin D was inversely related to BPPV incidence (RR = 1.36; 95% CI 1.31, 1.41), but not significantly related to the recurrence (RR = 0.95, 95% CI 0.91, 0.99); (3) Vitamin D supplementation group had a lower recurrence rate than the control group which did not accepted vitamin D supplementation (RR =0.45, 95% CI = 0.36–0.55).ConclusionThe serum level of vitamin D is lower in patients with BPPV, especially recurrent BPPV, than in controls. There was a negative correlation between occurrence rate of BPPV episodes and vitamin D deficiency, which means that vitamin D deficiency may have a role in occurrence of BPPV. The present study indicates that vitamin D supplementation can significantly lower recurrence in benign paroxysmal positional vertigo. The level of vitamin D was lower in canalolithiasis than in cupulolithiasis BPPV groups.